VP24 matrix proteins of eight filoviruses downregulate innate immune response by inhibiting the interferon-induced pathway - Khan Hira; Tripathi Lav; Kolehmainen Pekka; Lundberg Rickard; Altan Eda; Heroum Jemna; Julkunen Ilkka; Kakkola Laura; Huttunen Moona (The Microbiology Society, 2025)
Filoviruses encode viral protein 24 (VP24) which effectively inhibit the innate immune responses in infected cells. Here we systematically analysed the effects of nine mammalian filovirus VP24 proteins on interferon (IFN)-induced immune response. We transiently expressed Ebola, Bombali, Bundibugyo, Reston, Sudan and Taï Forest ebolavirus (EBOV, BOMV, BDBV, RESTV, SUDV, TAFV, respectively), Lloviu virus (LLOV), Mengla dianlovirus (MLAV) and Marburgvirus (MARV) VP24 proteins and analysed their ability to inhibit IFN-α-induced activation of myxovirus resistance protein 1 (MxA) and interferon-induced transmembrane protein 3 (IFITM3) promoters. In addition, we analysed the expression of endogenous MxA protein in filovirus VP24-expressing cells. Eight filovirus VP24 proteins, including the VP24s of the recently discovered MLAV, BOMV and LLOV, inhibited IFN-induced MxA and IFITM3 promoter activation. MARV VP24 was the only protein with no inhibitory effect on the activation of either promoter. Endogenous MxA protein expression was impaired in cells transiently expressing VP24s with the exception of MARV VP24. We mutated nuclear localization signal (NLS) of two highly pathogenic filoviruses (EBOV and SUDV) and two putatively non-pathogenic filoviruses (BOMV and RESTV), and showed that the inhibitory effect on IFN-induced expression of MxA was dependent on functional cluster 3 of VP24 nuclear localization signal. Our findings suggest that filovirus VP24 proteins are both genetically and functionally conserved, and that VP24 proteins of most filovirus species are capable of inhibiting IFN-induced antiviral gene expression thereby efficiently downregulating the host innate immune responses.